A4_4 Magnetic field alignments for nuclear fusion - Conlon, Thomas; Barker, Joshua; Coxon, John (Physics Special Topics, 2011)
This article considers two different configurations of magnetic field that could be used for magnetically confined nuclear fusion and considers whether using magnetic pressure to confine the plasma would allow a magnetic field of reasonable strength to be used. It was found that a feasible magnetic field strength (0.18 T) would be required to constrain the particles with an average energy, but it leaves the calculation regarding more energetic particles for further work.